Use of positive behaviour support plan for challenging behaviour in autism. Issue 4 (9th November 2020) - Javaid, Amir; Ghebru, Sium; Nawaz, Jabran; Michael, Dasari; Pearson, Richard; Rushforth, Emma; Michael, Gabriel
Abstract : The aim of a positive behaviour support (PBS) plan is to improve the quality of a person's life by supporting the person to lead a meaningful life and learn new skills without unnecessary restrictions. PBS uses person‐centred values as well as behavioural science and evidence to inform how to work with people who are at risk of displaying behaviour that challenges. Here, the authors describe how a PBS was effectively used to reduce anxiety and challenging behaviour in a person with autism.